2019
DOI: 10.1128/jvi.01465-18
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Neutralizing Monoclonal Antibodies to Human Astrovirus and Characterization of Virus Variants That Escape Neutralization

Abstract: Human astroviruses (HAstVs) cause severe diarrhea and represent an important health problem in children under two years of age. Despite their medical importance, the study of these pathogens has been neglected. To better understand the astrovirus antigenic structure and the basis of protective immunity, in this work we produced a panel of neutralizing monoclonal antibodies (Nt-MAbs) to HAstV serotypes 1, 2, and 8 and identified the mutations that allow the viruses to escape neutralization. We first tested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 18 publications
4
48
0
Order By: Relevance
“…Next, we tested the ability of the recombinant chimeric mAb 2D9 to bind its antigen, Spike 8, the recombinant capsid spike domain from human astrovirus serotype 8, against which mouse mAb 2D9 was raised. [25] By indirect ELISA, we found that both chimeric mAb 2D9 and mouse mAb 2D9 bind Spike 8 (Fig 4B and 4C). The other four chimeric mAbs also bind the human astrovirus spike against which they were raised.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Next, we tested the ability of the recombinant chimeric mAb 2D9 to bind its antigen, Spike 8, the recombinant capsid spike domain from human astrovirus serotype 8, against which mouse mAb 2D9 was raised. [25] By indirect ELISA, we found that both chimeric mAb 2D9 and mouse mAb 2D9 bind Spike 8 (Fig 4B and 4C). The other four chimeric mAbs also bind the human astrovirus spike against which they were raised.…”
Section: Resultsmentioning
confidence: 93%
“…To sequence the variable regions of five mouse monoclonal IgG1 antibodies (2D9, 3B4, 3E8, 3H4, and 4B6),[25] we extracted total RNA from the hybridoma cell lines expressing these antibodies and applied a modified RT-PCR (reverse transcription polymerase chain reaction) using SMART (switching mechanism at 5' end of RNA transcript) technology. [26, 27] This technology is based on the intrinsic features of the reverse transcriptase from the Moloney murine leukemia virus (MMLV) and the application of a custom-sequence template-switch oligonucleotide (template-switch oligo) forward primer containing 3 riboguanines (rGrGrG) at its 3' end.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The capsid of the mature, infectious virus has an icosahedral morphology of T = 3 and is composed of two proteins: VP34, which forms the shell of the virus particle (core protein), and VP27, a protein that constitutes the 30 dimeric globular spikes that protrude from the virion (spike protein) [ 3 ]. The spike protein, but not the core protein, has been shown to induce neutralizing antibodies [ 4 ] and several neutralizing antigenic determinants have been mapped on the spike, defined either by X-ray crystallography [ 5 ] or by sequencing HAstV-1, -2, and -8 mutants that escape neutralization by monoclonal neutralizing antibodies [ 4 ]. In addition, the HAstV spike has been shown to specifically bind to the surface of Caco-2 cells and to contain the receptor-binding domain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…HAstV has been shown to enter cells by clathrin-mediated endocytosis [ 6 ]; however, very little is known about the viral receptor or other cell factors that may determine virus entry. In this work we took advantage to the fact that the astrovirus capsid core and spike proteins can be successfully produced in Escherichia coli while maintaining their native structure [ 4 , 7 , 8 ] to identify interacting cellular proteins relevant for HAstV infection using a far-Western blotting approach. We found protein disulfide isomerase A4 (PDIA4) is an entry factor associated with genome uncoating of HAstV serotypes 1 and 8.…”
Section: Introductionmentioning
confidence: 99%